Analysis of the impact of growing green walls based on the reduction of PM2.5 particles in the resilient central urban fabric - Borna, Mohadese; Yeganeh, Mansour (Frontiers in Built Environment, 2024)
The problems of today’s world, particularly climate change and air pollution, require the search for sustainable and green buildings in urban environments and the people who inhabit them. General population and construction industry has emitted pollutants such as carbon dioxide to the atmosphere due to urbanization and rise in vehicles. In addition to that, the products employed in construction express a caliber of polluting the air. Urban facades and the materials used for construction in cities can often have a significant impact on aggravating air pollution. The implementation of green walls on building’s facade and other structures can be considered as the proper substitute to utilizing the stone and cement as those materials minimize the emission of air pollutants and add the better aesthetics to the city environment. The main objectives of this research are to describe and introduce a new method of applying green facades for buildings and structures using plants which have even greater abilities at absorbing pollutants and are simpler in application and management in comparison with other systems of green walls. In the first stage, the known green wall systems and along with suitable plants were introduced and studied through library studies and accordingly the most compatible plants for the studied area, considering the climate of Iran, specially Tehran which is the most polluted city in Iran, were identified. The ENVI-met application was used subsequently to determine the most appropriate model or plant to combat the pollutants in the environment.